Bayesian Network Modeling of Family Stress, Economic Pressure, and Child Adjustment Outcomes - Solbakken, Ingrid; Chennoufi, Amira (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The objective of this study was to identify and quantify the probabilistic pathways through which economic pressure and family stress influence multiple domains of child adjustment within Tunisian families using Bayesian network modeling. Methods and Materials: This cross-sectional study was conducted with 416 families recruited from urban and semi-urban regions of Tunisia, each consisting of one primary caregiver and one child aged 9–14 years. Data were collected using standardized, culturally adapted measures assessing economic pressure, family stress, and child emotional, behavioral, social, and prosocial adjustment. A multi-informant protocol was implemented, combining caregiver reports, child self-reports, and demographic questionnaires. Bayesian network analysis was applied to model conditional dependencies among study variables. Structure learning employed a hybrid constraint-based and score-based algorithm, and parameter estimation was performed using Bayesian inference. Model stability was examined through bootstrap resampling, and predictive validity was evaluated using k-fold cross-validation and classification accuracy indices. Findings: The Bayesian network revealed a dominant pathway from economic pressure to family stress with high posterior probability, followed by strong conditional effects of family stress on child emotional problems, conduct problems, peer difficulties, and prosocial behavior. Family stress emerged as the central mediating construct linking economic conditions to child outcomes. Emotional problems functioned as a key transmission node predicting peer difficulties. The model demonstrated high predictive accuracy across all child adjustment domains, with excellent discrimination between high-risk and low-risk profiles. Conclusion: The findings confirm that economic pressure exerts pervasive influence on child development primarily through its impact on family stress processes.